Gel electrolyte precursor and preparation thereof, gel electrolyte and lithium metal battery
The gel electrolyte prepared by in-situ polymerization method combines lithium salts, organic solvents, crosslinker monomers and thermal initiators to solve the problem of poor interface contact between lithium dendrites and electrolytes in lithium metal batteries, achieving efficient lithium ion migration and battery performance improvement.
Patent Information
- Application Number
- CN202510370549.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-27
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-03-27
AI Technical Summary
In practical applications, lithium metal batteries have safety problems such as side reactions between electrolyte and metal lithium, uneven deposition of lithium ions to form lithium dendrites, and the ionic conductivity of solid electrolytes is relatively low and the contact between electrodes is poor.
Gel electrolytes are prepared by in-situ polymerization method, and a gel electrolyte with a certain mechanical strength is formed by combining lithium salts, organic solvents, crosslinking agent monomers and thermal initiators, and is used in lithium metal batteries.
The gel electrolyte with high ionic conductivity, good mechanical flexibility and wide electrochemical window has good compatibility and interface stability, inhibits the growth of lithium dendrites, and improves the stable cycle time and low overpotential of lithium symmetric batteries.
Smart Images

Figure CN119875042A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a gel electrolyte precursor and a preparation method thereof, a gel electrolyte and a lithium metal battery, belonging to the technical field of new energy batteries. Background Art
[0002] The rapid development of electronic devices and electric vehicles has brought greater challenges to the energy system. In order to meet the needs of long-range driving, people are in urgent need of batteries with higher energy density. Metallic lithium has the advantages of high theoretical specific capacity and low reduction potential, and is one of the ideal negative electrode materials for high-energy-density lithium batteries. However, lithium metal batteries also have some problems in practical applications. The battery assembly environment is demanding, the electrolyte reacts with metallic lithium, and during the use of the battery, lithium ions are unevenly deposited on the surface of metallic lithium to form a large number of lithium dendrites, leading to safety issues. Solid electrolytes have certain mechanical strength and inhibit the growth of lithium dendrites to a certain extent, but there are problems with low ionic conductivity and poor interface contact with the electrode.
[0003] In-situ polymerization gel electrolyte batteries are expected to be an ideal solution to the above problems. Liquid electrolytes have the advantages of high conductivity, perfect wettability and maximized electrolyte / electrode contact area, while solid electrolytes have the advantage of high safety. Gel electrolytes prepared by in-situ polymerization are expected to combine the advantages of both while reducing their disadvantages. The gel electrolyte formed inside the battery by in-situ polymerization has the characteristics of low viscosity, easy handling, and strong wetting ability. It can fully infiltrate the active material and produce an ideal interface contact, thereby obtaining a good ion migration path and inhibiting the growth of lithium dendrites. Summary of the invention
[0004] In view of the problems existing in the prior art, the present invention provides a gel electrolyte precursor and a preparation method thereof, a gel electrolyte and a lithium metal battery.
[0005] The technical solution of the present invention to solve the above technical problems is as follows:
[0006] In a first aspect, the present invention provides a gel electrolyte precursor, which includes a lithium salt, an organic solvent, a crosslinking agent monomer and a thermal initiator, wherein the lithium salt includes lithium nitrate and lithium bis(trifluoromethanesulfonyl)imide, the organic solvent is a mixed solvent composed of ethylene glycol dimethyl ether and 1,3-dioxolane, the crosslinking agent monomer includes polyethylene glycol diacrylate or 1-vinylimidazole bis(trifluoromethanesulfonyl)imide, and the mass percentage of polyethylene glycol diacrylate or 1-vinylimidazole bis(trifluoromethanesulfonyl)imide in the crosslinking agent monomer is more than 75%; in a liquid electrolyte composed of a lithium salt and an organic solvent, the concentrations of lithium bis(trifluoromethanesulfonyl)imide and lithium nitrate are 230-340 mg / mL and 20-50 mg / mL, respectively; the masses of the crosslinking agent monomer and the thermal initiator account for 8-20% and 0.08-0.2% of the total mass of the gel electrolyte precursor, respectively.
[0007] Preferably, in the mixed solvent of ethylene glycol dimethyl ether and 1,3-dioxolane, the volume ratio of ethylene glycol dimethyl ether to 1,3-dioxolane is 1:0.5-2, most preferably 1:1.
[0008] Preferably, the thermal initiator is an azo thermal initiator, such as azobisisobutyronitrile.
[0009] Preferably, the crosslinking agent monomer further comprises at least one of pentaerythritol tetraacrylate, ethoxylated trimethylolpropane triacrylate and triethylene glycol diacrylate.
[0010] Preferably, in the liquid electrolyte composed of a lithium salt and an organic solvent, the concentrations of lithium bis(trifluoromethanesulfonyl)imide and lithium nitrate are 273-301 mg / mL and 48-53 mg / mL, respectively, and more preferably 287.1 mg / mL and 50 mg / mL.
[0011] Preferably, the lithium salt further comprises lithium difluorooxalate borate, and in the liquid electrolyte composed of the lithium salt and the organic solvent, the concentration of lithium difluorooxalate borate is 14-43 mg mL -1 , more preferably 27-30 mg / mL.
[0012] Preferably, the crosslinking agent monomer is polyethylene glycol diacrylate or a combination of polyethylene glycol diacrylate and at least one of pentaerythritol tetraacrylate, ethoxylated trimethylolpropane triacrylate and triethylene glycol diacrylate; the lithium salt is composed of lithium bis(trifluoromethanesulfonyl imide), lithium difluorooxalate borate and lithium nitrate; in a liquid electrolyte composed of a lithium salt and an organic solvent, the concentrations of lithium bis(trifluoromethanesulfonyl imide), lithium difluorooxalate borate and lithium nitrate are 273-301 mg / mL, 27-30 mg / mL and 48-53 mg / mL, respectively; more preferably, the concentrations of lithium bis(trifluoromethanesulfonyl imide, lithium difluorooxalate borate and lithium nitrate are 273-301 mg / mL, 27-30 mg / mL and 50 mg / mL, respectively; and more preferably, the concentrations of lithium bis(trifluoromethanesulfonyl imide, lithium difluorooxalate borate and lithium nitrate are 287.1 mg / mL, 28.8 mg / mL and 50 mg / mL.
[0013] Preferably, the crosslinking agent monomer is 1-vinylimidazole bis(trifluoromethanesulfonyl)imide, the lithium salt is composed of lithium bis(trifluoromethanesulfonyl)imide and lithium nitrate, and in the liquid electrolyte composed of lithium salt and organic solvent, the concentrations of lithium bis(trifluoromethanesulfonyl)imide and lithium nitrate are 273-301 mg / mL and 48-53 mg / mL, respectively, more preferably 273-301 mg / mL and 50 mg / mL, and further preferably 287.1 mg / mL and 50 mg / mL;
[0014] Alternatively, the lithium salt consists of lithium bis(trifluoromethanesulfonyl imide), lithium difluorooxalatoborate and lithium nitrate. In a liquid electrolyte consisting of a lithium salt and an organic solvent, the concentrations of lithium bis(trifluoromethanesulfonyl imide), lithium difluorooxalatoborate and lithium nitrate are 273-301 mg / mL, 27-30 mg / mL and 48-53 mg / mL, respectively, more preferably 273-301 mg / mL, 27-30 mg / mL and 50 mg / mL, and even more preferably 287.1 mg / mL, 28.8 mg / mL and 50 mg / mL.
[0015] Preferably, the weight of the crosslinking agent monomer and the thermal initiator account for 14-16% and 0.14-0.16% of the total weight of the gel electrolyte precursor, respectively.
[0016] Preferably, the gel electrolyte precursor consists of a lithium salt, an organic solvent, a cross-linking agent monomer and a thermal initiator.
[0017] In a second aspect, the present invention provides a method for preparing the gel electrolyte precursor described in the first aspect, the preparation method comprising: dissolving a lithium salt in an organic solvent, and stirring the mixture to obtain a liquid electrolyte; adding a crosslinking agent monomer and a thermal initiator to the liquid electrolyte, and stirring the mixture to obtain a gel electrolyte precursor.
[0018] In a third aspect, the present invention provides a gel electrolyte obtained by thermally initiating in-situ free radical polymerization of the gel electrolyte precursor described in the first aspect.
[0019] Preferably, the polymerization conditions are: polymerization temperature is 50-70° C., more preferably 60° C.; polymerization time is 2-12 h, more preferably 4-7 h, further preferably 6 h.
[0020] In a fourth aspect, the present invention provides a lithium metal battery, comprising a positive electrode, a negative electrode and an electrolyte, wherein the electrolyte is the gel electrolyte described in the third aspect.
[0021] In the lithium metal battery, the positive electrode and the negative electrode can be the positive electrode and the negative electrode conventionally used in lithium metal batteries, and the assembly method can also be carried out in a conventional manner.
[0022] Compared with the prior art, the present invention has the following beneficial effects: the present invention uses an in-situ polymerization technology to prepare a gel electrolyte with a certain mechanical strength through a preferred combination of lithium salt, organic solvent, and cross-linking agent monomer, and is applied to lithium metal batteries. The beneficial effects are:
[0023] 1. The gel electrolyte of the present invention has high ionic conductivity, good mechanical flexibility and wide electrochemical window. The gel electrolyte has good compatibility, interface stability and low interface impedance with metallic lithium. Side reactions are effectively suppressed, thereby showing high stable cycle time and low overpotential in lithium symmetric batteries.
[0024] 2. The lithium metal full battery prepared by the gel electrolyte of the present invention has good cycle stability, capacity retention rate and coulombic efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is an optical photograph of the in-situ polymerized gel electrolyte prepared in Example 1 of the present invention.
[0026] Figure 2 This is a test graph of the lithium ion migration number of the in-situ polymerized gel electrolyte prepared in Example 1 of the present invention.
[0027] Figure 3 It is a comparison chart of the cycle tests of the lithium symmetric batteries prepared in Example 1 (adding LiDFOB) and Example 6 (not adding LiDFOB) of the present invention.
[0028] Figure 4 It is a comparison chart of cycle tests of lithium iron phosphate batteries prepared in Example 1 (i.e., gel electrolyte) of the present invention and Comparative Example 1 (i.e., liquid electrolyte).
[0029] Figure 5 This is a cycle test diagram of the lithium iron phosphate battery prepared in Example 1 of the present invention.
[0030] Figure 6 This is a first cycle capacity-voltage curve of the lithium iron phosphate||lithium battery prepared in Example 2 of the present invention.
[0031] Figure 7 It is a linear sweep voltammetry curve of the in-situ polymerized gel electrolyte prepared in Example 4 of the present invention.
[0032] Figure 8 This is a cycle test diagram of the lithium symmetrical battery prepared in Example 4 of the present invention.
[0033] Fig. 9 This is a test graph of the ionic conductivity of the in-situ polymerized gel electrolyte prepared in Example 5 of the present invention.
[0034] Fig.10 This is a cycle test chart of the lithium iron phosphate battery prepared in Example 5 of the present invention. DETAILED DESCRIPTION
[0035] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0036] Battery assembly: CR2032 button cells were assembled in a glove box filled with argon. The positive electrode sheet was placed in the positive electrode shell, a glass fiber separator was placed, 50 μL of in-situ polymerized gel electrolyte precursor was added, and then the negative electrode sheet, stainless steel gasket, stainless steel spring, and negative electrode shell were placed in order, and finally pressed and sealed on a sealing machine.
[0037] An in-situ polymerized gel electrolyte prepared in the following example was tested as follows: wherein the test temperature was 30°C.
[0038] 1. The ionic conductivity of the in-situ polymerized gel electrolyte was tested by using an AC impedance method.
[0039] The test system was assembled into a stainless steel symmetrical cell, and the electrochemical impedance spectroscopy (EIS) test was selected on a CHI660E electrochemical workstation with a frequency range of 10 -1 -10 6 Hz.
[0040] 2. Use AC impedance method to test the impedance of lithium symmetrical battery.
[0041] The test system was assembled into a lithium symmetric battery, and the electrochemical impedance spectroscopy (EIS) test was selected on the CHI660E electrochemical workstation with a frequency range of 10 -1 -10 6 Hz.
[0042] 3. The lithium ion migration number of the in-situ polymerized gel electrolyte was tested by chronoamperometry.
[0043] The test system was assembled into a lithium symmetric battery, and the chronoamperometric (IT) test was selected on the CHI660E electrochemical workstation with a voltage of 10 mV and a time of 1200 s.
[0044] 4. The electrochemical window of the in-situ polymerized gel electrolyte was tested by linear sweep voltammetry.
[0045] The test system was assembled into a stainless steel||lithium battery, and a linear sweep voltammetry test was selected on a CHI660E electrochemical workstation with a voltage range of -5.5 V, the open circuit voltage of the battery.
[0046] The test system was assembled into a lithium iron phosphate battery. The lithium iron phosphate electrode was purchased from Cluder, and the coating surface density was 12.3 mg cm -2 Cyclic voltammetry was performed on a CHI660E electrochemical workstation with a voltage range of 2.5–4.2 V.
[0047] 5. Charge and discharge cycle performance test.
[0048] The battery is charged and discharged using the Xinwei battery test system. The test contents mainly include:
[0049] (1) Lithium symmetric battery at 0.5 mA cm -2 The current density is 0.5 mAh cm -2 Lithium deposition / stripping cycle tests were carried out at a surface capacity of .
[0050] (2) Lithium iron phosphate||The cycle stability, capacity retention rate, coulombic efficiency, etc. of lithium batteries were tested at 0.2C and 0.5C rates with a voltage range of 2.5-4.2V.
[0051] Example 1
[0052] 1) Lithium nitrate, lithium bis(trifluoromethanesulfonyl imide), and lithium difluorooxalatoborate were added to an equal volume mixed solvent of ethylene glycol dimethyl ether and 1,3-dioxolane and stirred thoroughly to obtain a liquid electrolyte; wherein the concentration of lithium nitrate was 50 mg / mL -1 , the concentration of lithium bis(trifluoromethanesulfonyl)imide was 287.1 mg mL -1, the concentration of lithium difluorooxalate borate is 28.8 mgmL -1 ; The stirring speed was 400 rpm and the stirring time was 4 h.
[0053] 2) Adding polyethylene glycol diacrylate monomer and azobisisobutyronitrile to the liquid electrolyte prepared in step 1) and stirring thoroughly to obtain an in-situ polymerized gel electrolyte precursor solution; wherein polyethylene glycol diacrylate accounts for 15% of the total mass of the in-situ polymerized gel electrolyte, and azobisisobutyronitrile accounts for 0.15% of the total mass of the in-situ polymerized gel electrolyte; the stirring speed is 400 rpm, and the stirring time is 4 h.
[0054] 3) heating the in-situ polymerized gel electrolyte precursor solution prepared in step 2) to initiate a cross-linking polymerization reaction, thereby obtaining an in-situ polymerized gel electrolyte; wherein the heating temperature is 60° C. and the heating time is 6 h.
[0055] Figure 1 It is an optical photograph of the in-situ polymerized gel electrolyte of Example 1 of the present invention; the in-situ polymerized gel electrolyte in this example is yellow.
[0056] Figure 2 This is a test graph of the lithium ion migration number of the in-situ polymerized gel electrolyte of Example 1 of the present invention; based on the current and interface impedance values in the steady state and initial state, it is calculated that the lithium ion migration number can reach 0.68; a higher lithium ion migration number means that during the charge and discharge process, lithium ions can be more efficiently transferred between the positive and negative electrodes.
[0057] Figure 3 It is a comparison chart of the deposition / stripping cycle test of the lithium symmetric battery of Example 1 of the present invention and Comparative Example 1; the lithium symmetric battery of Example 1 can be stably cycled for 3000 h, and the overpotential can be maintained at about 11 mV for a long time.
[0058] Figure 4 The comparison chart of the cycle test of the lithium iron phosphate||lithium battery of Example 1 of the present invention and Comparative Example 2, the charge and discharge rate is 0.2 C; the first cycle discharge capacity of the battery of Example 1 is 169.3 mAh g -1 The first-cycle Coulomb efficiency is 96.8%, and the capacity retention rate is still 82.3% after 200 cycles.
[0059] Figure 5 This is a cycle test diagram of the lithium iron phosphate||lithium battery of Example 1 of the present invention; at a discharge rate of 0.5 C, the first cycle discharge specific capacity of the battery of Example 1 is 160.2 mAh g -1 The first-cycle Coulomb efficiency is 96.1%, and the capacity retention rate is still 91.2% after 100 cycles.
[0060] The ionic conductivity of the in-situ polymerized gel electrolyte prepared in this example is 2.1×10 -3 S cm -1 , the electrochemical window is 4.7 V.
[0061] Example 2
[0062] 1) Add lithium nitrate, lithium bis(trifluoromethanesulfonyl imide), and lithium difluorooxalatoborate to an equal volume mixed solvent of ethylene glycol dimethyl ether and 1,3-dioxolane and stir thoroughly to obtain a liquid electrolyte; wherein the concentration of lithium nitrate is 20 mg / mL -1 , the concentration of lithium bis(trifluoromethanesulfonyl)imide was 287.1 mg mL -1 , the concentration of lithium difluorooxalate borate is 28.8 mgmL -1 ; The stirring speed was 400 rpm and the stirring time was 4 h.
[0063] 2) Adding polyethylene glycol diacrylate monomer and azobisisobutyronitrile to the liquid electrolyte prepared in step 1) and stirring thoroughly to obtain an in-situ polymerized gel electrolyte precursor solution; wherein polyethylene glycol diacrylate accounts for 15% of the total mass of the in-situ polymerized gel electrolyte, and azobisisobutyronitrile accounts for 0.15% of the total mass of the in-situ polymerized gel electrolyte; the stirring speed is 400 rpm, and the stirring time is 4 h.
[0064] 3) heating the in-situ polymerized gel electrolyte precursor solution prepared in step 2) to initiate a cross-linking polymerization reaction, thereby obtaining an in-situ polymerized gel electrolyte; wherein the heating temperature is 60° C. and the heating time is 6 h.
[0065] Figure 6 The first cycle capacity-voltage curve of the lithium metal battery prepared in Example 2 of the present invention is shown in FIG. 1 . The in-situ polymerized gel electrolyte prepared in this example is yellow. The lithium symmetric battery can be stably cycled for 1000 h. When discharged at a rate of 0.2 C, the first cycle discharge specific capacity of the lithium iron phosphate||lithium battery is 160.3 mAh g -1 , the first-cycle Coulomb efficiency is 94.3%.
[0066] Example 3
[0067] 1) Lithium nitrate, lithium bis(trifluoromethanesulfonyl imide), and lithium difluorooxalatoborate were added to an equal volume mixed solvent of ethylene glycol dimethyl ether and 1,3-dioxolane and stirred thoroughly to obtain a liquid electrolyte; wherein the concentration of lithium nitrate was 50 mg / mL -1 , the concentration of lithium bis(trifluoromethanesulfonyl)imide was 287.1 mg mL -1 , the concentration of lithium difluorooxalate borate is 28.8 mgmL -1; The stirring speed was 400 rpm and the stirring time was 4 h.
[0068] 2) Adding polyethylene glycol diacrylate monomer, pentaerythritol tetraacrylate monomer and azobisisobutyronitrile to the liquid electrolyte prepared in step 1) and stirring thoroughly to obtain an in-situ polymerized gel electrolyte precursor solution; wherein polyethylene glycol diacrylate accounts for 12% of the total mass of the in-situ polymerized gel electrolyte, pentaerythritol tetraacrylate accounts for 3% of the total mass of the in-situ polymerized gel electrolyte, and azobisisobutyronitrile accounts for 0.15% of the total mass of the in-situ polymerized gel electrolyte; the stirring speed is 400 rpm, and the stirring time is 4 h.
[0069] 3) heating the in-situ polymerized gel electrolyte precursor solution prepared in step 2) to initiate a cross-linking polymerization reaction, thereby obtaining an in-situ polymerized gel electrolyte; wherein the heating temperature is 60° C. and the heating time is 6 h.
[0070] The in-situ polymerized gel electrolyte prepared in this embodiment is yellow; the lithium symmetric battery can be stably cycled for 2500 h, and the overpotential can be maintained at about 7 mV for a long time; at a discharge rate of 0.2 C, the first cycle discharge capacity of the lithium iron phosphate||lithium battery is 157.1 mAh g -1 The first-cycle Coulomb efficiency is 96.5%, and the capacity retention rate is still 75.5% after 180 cycles.
[0071] Example 4
[0072] 1) Add lithium nitrate and lithium bis(trifluoromethanesulfonyl imide) to an equal volume mixed solvent of ethylene glycol dimethyl ether and 1,3-dioxolane and stir thoroughly to obtain a liquid electrolyte; wherein the concentration of lithium nitrate is 50 mg mL -1 , the concentration of lithium bis(trifluoromethanesulfonyl)imide was 287.1 mg mL -1 ; The stirring speed was 400 rpm and the stirring time was 4 h.
[0073] 2) Adding 1-vinylimidazole bis(trifluoromethanesulfonyl)imide monomer and azobisisobutyronitrile to the liquid electrolyte prepared in step 1) and stirring thoroughly to obtain an in-situ polymerized gel electrolyte precursor solution; wherein 1-vinylimidazole bis(trifluoromethanesulfonyl)imide accounts for 15% of the total mass of the in-situ polymerized gel electrolyte, and azobisisobutyronitrile accounts for 0.15% of the total mass of the in-situ polymerized gel electrolyte; the stirring speed is 400 rpm, and the stirring time is 4 h.
[0074] 3) heating the in-situ polymerized gel electrolyte precursor solution prepared in step 2) to initiate a cross-linking polymerization reaction, thereby obtaining an in-situ polymerized gel electrolyte; wherein the heating temperature is 60° C. and the heating time is 6 h.
[0075] Figure 7 3 is a linear sweep voltammetry curve of the in-situ polymerized gel electrolyte prepared in Example 4 of the present invention; the electrochemical window of the gel electrolyte can reach 5.0 V.
[0076] Figure 8 It is a cycle test diagram of the lithium symmetric battery prepared in Example 4 of the present invention; the lithium symmetric battery in Example 4 can be stably cycled for 700 h.
[0077] The in-situ polymerized gel electrolyte prepared in this embodiment is colorless; when discharged at a rate of 0.5 C, the first cycle discharge capacity of the lithium iron phosphate||lithium battery is 158.0 mAh g -1 The first-cycle Coulomb efficiency is 93.6%, and the capacity retention rate is still 75.8% after 100 cycles.
[0078] Example 5
[0079] 1) Lithium nitrate, lithium bis(trifluoromethanesulfonyl imide), and lithium difluorooxalatoborate were added to an equal volume mixed solvent of ethylene glycol dimethyl ether and 1,3-dioxolane and stirred thoroughly to obtain a liquid electrolyte; wherein the concentration of lithium nitrate was 50 mg / mL -1 , the concentration of lithium bis(trifluoromethanesulfonyl)imide was 287.1 mg mL -1 , the concentration of lithium difluorooxalate borate is 28.8 mgmL -1 ; The stirring speed was 400 rpm and the stirring time was 4 h.
[0080] 2) Adding 1-vinylimidazole bis(trifluoromethanesulfonyl)imide monomer and azobisisobutyronitrile to the liquid electrolyte prepared in step 1) and stirring thoroughly to obtain an in-situ polymerized gel electrolyte precursor solution; wherein 1-vinylimidazole bis(trifluoromethanesulfonyl)imide accounts for 15% of the total mass of the in-situ polymerized gel electrolyte, and azobisisobutyronitrile accounts for 0.15% of the total mass of the in-situ polymerized gel electrolyte; the stirring speed is 400 rpm, and the stirring time is 4 h.
[0081] 3) heating the in-situ polymerized gel electrolyte precursor solution prepared in step 2) to initiate a cross-linking polymerization reaction, thereby obtaining an in-situ polymerized gel electrolyte; wherein the heating temperature is 60° C. and the heating time is 6 h.
[0082] Fig. 9 This is a test graph of the ionic conductivity of the in-situ polymerized gel electrolyte prepared in Example 5 of the present invention; the ionic conductivity of the gel electrolyte can reach 4.0×10 -3 S cm -1 ; Higher ionic conductivity provides a positive effect on the lithium ion transport of the battery, promotes the battery's cycle stability, and extends the battery life.
[0083] Fig.10 This is a cycle test diagram of the lithium iron phosphate||lithium battery prepared in Example 5 of the present invention; at a discharge rate of 0.5 C, the first cycle discharge specific capacity of the lithium iron phosphate||lithium battery is 155.0 mAh g -1 The first-cycle coulomb efficiency is 95.0%, and the capacity retention rate is still 77.7% after 100 cycles.
[0084] The in-situ polymerized gel electrolyte prepared in this example is colorless; the lithium symmetric battery can be stably cycled for 80 h.
[0085] Example 6
[0086] The in-situ polymerized gel electrolyte was prepared by the same method as in Example 1, except that lithium difluorooxalatoborate was not added in this example.
[0087] The in-situ polymerized gel electrolyte prepared in this embodiment is yellow; Figure 3 As shown in the figure, the lithium symmetric battery can be stably cycled for 1000 h, and the overpotential can be maintained at about 13 mV for a long time. When discharged at a rate of 0.2 C, the first cycle discharge capacity of the lithium iron phosphate||lithium battery is 163.0 mAh g -1 The first cycle coulomb efficiency is 95.3%, and the capacity retention rate is 85.1% after 40 cycles.
[0088] From the comparison of the experimental data of Example 6 and Example 1, it can be seen that: when preparing the gel electrolyte, if lithium difluorooxalatoborate is not added, the lithium symmetric battery still shows good cycle stability for metallic lithium and low overpotential; however, if lithium difluorooxalatoborate is not added, the performance of the entire battery will be reduced, because the gel electrolyte without the participation of lithium difluorooxalatoborate cannot form a stable boron-containing interface film at the negative electrode, and the positive electrode current collector is corroded, thereby causing the battery performance to decay.
[0089] Comparative Example 1
[0090] The liquid electrolyte was prepared using the method of step 1) in Example 1.
[0091] The liquid electrolyte prepared by this comparative example is colorless; Figure 4 As shown, the first cycle discharge capacity of lithium iron phosphate||lithium battery is 165.8 mAh g -1 The first cycle coulomb efficiency is 98.9%, and the capacity retention rate is 63.6% after 200 cycles.
[0092] From the comparison of the experimental data of Comparative Example 1 and Example 1, it can be seen that if polyethylene glycol diacrylate is not added during the preparation of the electrolyte, the battery performance will be reduced, because the liquid electrolyte without the participation of polyethylene glycol diacrylate does not have sufficient mechanical strength to inhibit the growth of lithium dendrites, thereby causing the battery performance to decay.
[0093] Comparative Example 2
[0094] The liquid electrolyte was prepared using the method of step 1) in Example 3.
[0095] The liquid electrolyte prepared by this comparative example is colorless; the electrochemical window is 4.7 V; the lithium symmetric battery can be stably cycled for 150 h; and the first cycle discharge capacity of the lithium iron phosphate||lithium battery is 161.3 mAh g at a discharge rate of 0.5 C. -1 The first cycle coulomb efficiency is 97.6%, and the capacity retention rate is 64.3% after 100 cycles.
[0096] From the comparison of the experimental data of Comparative Example 2 and Example 4, it can be seen that if 1-vinylimidazole bis(trifluoromethanesulfonyl)imide is not added during the preparation of the electrolyte, the battery performance will be reduced, because the liquid electrolyte without the participation of 1-vinylimidazole bis(trifluoromethanesulfonyl)imide does not have sufficient mechanical strength to inhibit the growth of lithium dendrites, thereby causing the battery performance to decay.
[0097] The technical features of the above-described embodiments may be combined arbitrarily, and the contents described are only preferred embodiments of the present invention. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope recorded in this specification. All equivalent changes and improvements made within the scope of application of the present invention should still fall within the scope of the patent coverage of the present invention.
Claims
1. A gel electrolyte precursor, characterized in that: The gel electrolyte precursor comprises a lithium salt, an organic solvent, a crosslinking agent monomer and a thermal initiator, wherein the lithium salt comprises lithium nitrate and lithium bis(trifluoromethanesulfonyl)imide, the organic solvent is a mixed solvent of ethylene glycol dimethyl ether and 1,3-dioxolane, the crosslinking agent monomer comprises polyethylene glycol diacrylate or 1-vinylimidazole bis(trifluoromethanesulfonyl)imide, and the mass percentage of polyethylene glycol diacrylate or 1-vinylimidazole bis(trifluoromethanesulfonyl)imide in the crosslinking agent monomer is more than 75%; in a liquid electrolyte composed of the lithium salt and the organic solvent, the concentrations of lithium bis(trifluoromethanesulfonyl)imide and lithium nitrate are 230-340 mg / mL and 20-50 mg / mL, respectively; the masses of the crosslinking agent monomer and the thermal initiator account for 8-20% and 0.08-0.2% of the total mass of the gel electrolyte precursor, respectively.
2. The gel electrolyte precursor according to claim 1, characterized in that: The thermal initiator is an azo thermal initiator.
3. The gel electrolyte precursor according to claim 1, characterized in that: The crosslinking agent monomer further comprises at least one of pentaerythritol tetraacrylate, ethoxylated trimethylolpropane triacrylate and triethylene glycol diacrylate.
4. The gel electrolyte precursor according to claim 1, characterized in that: The lithium salt also includes lithium difluorooxalate borate. In the liquid electrolyte composed of the lithium salt and the organic solvent, the concentration of the lithium difluorooxalate borate is 14-43 mg mL -1 .
5. The gel electrolyte precursor according to claim 1, characterized in that: The crosslinking agent monomer is polyethylene glycol diacrylate or a combination of polyethylene glycol diacrylate and at least one of pentaerythritol tetraacrylate, ethoxylated trimethylolpropane triacrylate and triethylene glycol diacrylate; the lithium salt is composed of lithium bis(trifluoromethanesulfonyl imide), lithium difluorooxalate borate and lithium nitrate; in a liquid electrolyte composed of lithium salt and an organic solvent, the concentrations of lithium bis(trifluoromethanesulfonyl imide), lithium difluorooxalate borate and lithium nitrate are 273-301 mg / mL, 27-30 mg / mL and 48-53 mg / mL, respectively; Alternatively, the crosslinking agent monomer is 1-vinylimidazole bis(trifluoromethanesulfonyl)imide, the lithium salt is composed of lithium bis(trifluoromethanesulfonyl)imide and lithium nitrate, and in a liquid electrolyte composed of a lithium salt and an organic solvent, the concentrations of lithium bis(trifluoromethanesulfonyl)imide and lithium nitrate are 273-301 mg / mL and 48-53 mg / mL, respectively; or the lithium salt is composed of lithium bis(trifluoromethanesulfonyl)imide, lithium difluorooxalate borate and lithium nitrate, and in a liquid electrolyte composed of a lithium salt and an organic solvent, the concentrations of lithium bis(trifluoromethanesulfonyl)imide, lithium difluorooxalate borate and lithium nitrate are 273-301 mg / mL, 27-30 mg / mL and 48-53 mg / mL, respectively.
6. The gel electrolyte precursor according to claim 1, characterized in that: The gel electrolyte precursor consists of lithium salt, organic solvent, crosslinking agent monomer and thermal initiator.
7. A method for preparing a gel electrolyte precursor according to any one of claims 1 to 6, characterized in that: The preparation method comprises: dissolving lithium salt in an organic solvent, and stirring the mixture to obtain a liquid electrolyte; adding a crosslinking agent monomer and a thermal initiator to the liquid electrolyte, and stirring the mixture to obtain a gel electrolyte precursor.
8. A gel electrolyte obtained by thermally initiating in-situ free radical polymerization of the gel electrolyte precursor according to any one of claims 1 to 6.
9. The gel electrolyte according to claim 8, characterized in that: The polymerization conditions are as follows: polymerization temperature is 50-70°C; polymerization time is 2-12 h.
10. A lithium metal battery comprising a positive electrode, a negative electrode and an electrolyte, characterized in that: The electrolyte is the gel electrolyte according to claim 8.
Citation Information
Patent Citations
Composite gel polymer electrolyte and preparation method and application thereof
CN110444807A
Polyion liquid electrolyte for in-situ photopolymerization without solvent
CN111490289A
Preparation method of polyethylene glycol diacrylate-based gel electrolyte
CN111554974A
Imidazole polyion liquid gel electrolyte and preparation method thereof
CN112185712A
Preparation method of semi-solid polyion liquid electrolyte for lithium battery
CN113429504A
Cited By
P (IL-PE) x gel electrolyte, and preparation method and application thereof
CN121812724A